Pollitical economy of policy reform in developing countries - Krueger, Anne O. (London, 1993)
In this examination of the political economy of economic policy determination and evolution in developing countries, Anne Krueger provides concrete insights into the interaction of economic and political variables that determine the success or failure of such policies an understanding that is essential if economists are to provide realistic technical assistance in the formulation of economic policy reform programs. The debt crisis of the 1980s accompanied an era of slow economic growth. Developing countries had widely divergent experiences. Some, like the East Asian countries, weathered the recession to resume and even accelerate growth and to lower their debt-servicing ratios. Others, like those in Africa and Latin America, fell into slow or even negative growth, were unable to tighten their debt burden, and experienced declines in per capita income. Krueger analyzes the interaction of politics and economics in experience with slow growth and debt crisis in terms of three major themes. The first is that politically determined policies have economic consequences that can and do change the political equilibrium that generated those policies. Second, the analysis of the political economy of economic policy determination in developed countries can only be undertaken on the basis of assumptions about the nature of government. These two themes, which have been taken up in current economics and political science literature, imply yet a third and less frequently noted proposition that neither economic policies or governments can be looked at as enduring phenomena. Both the nature of the government and the economic policies can be changed according to the political and economic responses one sets off in the other, resulting in various types of "policy cycles" that need to be better understood.
Keywords: Political science